SensorMap for Wide-Area Sensor Webs - Nath, Suman; Liu, Jie; Zhao, Feng (IEEE Computer, 2007)
Geocentric Web interfaces such as Microsoft Virtual Earth and Google Maps are useful for visualizing spatially and geographically related data such as driving directions, directory entries, and weather and traffic conditions, to name a few. The desire to add useful information to these interfaces has led developers to create custom applications that overlay housing prices, crime rates, bus locations, and other data on top of browsable maps. These applications are possible due to useful APIs that Google Maps and Microsoft Virtual Earth publish to overlay location data on maps.